Penyuluhan UU Nomor 35 Tahun 2014 Perubahan Atas UU Nomor 23 Tahun 2002 Tentang Perlindungan dan Hak Anak di Desa Pasaka - Martono; Syahrani Anugrah; Sitti Amalia; Alif Ikbal Maulana (YP-SDI Lamaddukelleng, 2024)
The village of Pasaka is located in the Sabbangparu subdistrict of the Wajo District. The community's average level of knowledge regarding the law remains relatively low, particularly among parents and adults in relation to child protection legislation. Indeed, there are some who are entirely uninformed on this matter. The enactment of Law No. 35/2014 on child protection represents a significant amendment to the preceding legislation, namely Law No. 23/2002. The objective of this new legislation is to reinforce the legal protection of children's rights within the Indonesian legal framework. The revised legislation introduces enhanced penalties for those convicted of crimes against children, while also reaffirming the pivotal roles of parents, the government and civil society in safeguarding the rights of the child. The law places an emphasis on the fulfilment of children's fundamental rights, including the right to life, development and participation. It is anticipated that this will result in the creation of a secure and favourable environment for children. By providing guidance on child protection legislation, the community will be better equipped to enhance their awareness, foster greater openness and sensitivity, and take action in instances of child abuse.